Considering Indonesia's Economic Growth Direction: Between the OECD and BRICS - Arief Rahman Maulana; Aswin Ariyanto Azis (International Journal Labs, 2025)
This research examines Indonesia's economic strategy in navigating simultaneous engagement with two major economic blocs, the Organisation for Economic Co-operation and Development (OECD) and BRICS, specifically analyzing the relevance of the OECD for Indonesia after BRICS membership amidst the dynamics of economic growth of OECD countries. This research aims to analyze the potential of Indonesia's economic strategy through a hedging concept approach within the framework of BRICS membership and accession to the OECD. Using descriptive-qualitative method based on literature study and secondary data, the patterns of cooperation and economic performance of the two blocs are analyzed. The results show that engagement with BRICS does not diminish the strategic role of the OECD, BRICS offers opportunities through market expansion and access to alternative financing, while the OECD remains vital as a partner to promote structural reforms and improve national competitiveness.